Wörter und Krieg: Ostap Slyvyns′kyjs „Slovnyk vijny“ im Kontext aktueller und historischer Kriegslyrik - Marszałek, Magdalena (Wiener Slawistischer Almanach, 2025)
The article addresses the question of how poetry reflects on language in times of war. The focus is on contemporary Ukrainian poetry in the context of the Russian invasion, in particular on Ostap Slyvyns′kyi’s Slovnyk vijny. This “Dictionary of War” represents a form of documentary that owes itself to a poetic sensitivity for the authentic spoken word. In his foreword, Slyvyns′kyi lays a trail to Polish war poetry, which is subjected to a closer reading. The crisis of language and writing during the war turns into the productivity of testimony.